Is Malaysia's Pension Scheme Sufficient to Secure the Quality of Life for the Elderly? - Isahaque Ali; Azlinda Azman; Zulkarnain A. Hatta; M. Rezaul Islam; A H M Belayeth Hussain (Social Work and Society, 2020)
The paper examined whether the current income provision for the elderly under Malaysia's pension scheme is sufficient to maintain the standard of living of pensioners vis-à-vis increasing competitive market prices. It employed a quantitative research approach by using social survey and semi-structured face-to-face interviews schedule to collect the data. Data were collected from 200 pensioners in the state of Penang, Malaysia, using satisfaction for the Quality of Life (QOL) index. Results showed that the mean score of satisfaction for QOL was 2.58 (SD.694) and that the pension scheme was insufficient to maintain the standard of living of pensioners when compared with their total cost. The study suggested modifying the current public pension scheme to increase the benefits to provide a minimum standard of living of the elderly in Malaysia.